A novel dual lock method for down-regulation of genes, in which a target mRNA is captured at 2 independent positions by linked locked nucleic acid antisense oligonucleotides. Issue 3 (3rd March 2016) - Takata, Ryohei; Makado, Gouki; Kitamura, Ayaka; Watanabe, Hajime; Wada, Tadashi
Abstract: Nuclear factor κB (NFκB), which is composed of the RelA and p50 subunits, binds to NFκB response elements (NREs) and stimulates the transcription of inflammation-related genes. Here, locked nucleic acid (LNA) antisense oligonucleotides (ASOs) complementary to the termini of the 3′- and 5′-untranslated regions (UTRs) of the RelA mRNA were generated; these molecules were named 3′-LNA and 5′-LNA, respectively. To evaluate their effects on NFκB activity, HeLa cells were co-transfected with the LNA ASOs and a luciferase reporter gene carrying an NRE. Transfection of the cells with 3′-LNA reduced NFκB activity by 30–40%, without affecting RelA mRNA accumulation. Concomitant transfection of HeLa cells with 5′-LNA and 3′-LNA resulted in a 70% reduction in NFκB activity. Furthermore, partial poly(A) tail shortening occurred in LNA ASO-transfected cells. We also employed triethylene glycol as a spacer to link 5′-LNA and 3′-LNA. Reporter gene assays showed that the spacer-linked LNA ASO reduced NFκB activity similarly to a combination of 5′-LNA and 3′-LNA. In addition, an in vitro translation assay revealed that spacer-linked LNA ASOs inhibited the translation of a target mRNA in a specific manner. In summary, this study describes a novel antisense method capturing the target mRNA at independent positions.